Densidades de semeadura de leguminosas na melhoria da qualidade do solo e na produtividade do milho - Melo, Isabel Giovanna Costa e (Universidade Federal Rural do Semi-Árido, 2015)
Currently, the concern with the progress of degradation processes installed in most Brazilian soils, and with the prevention of the degradation of new areas, has led to the need to use practices to add organic matter to soil. Among these, there is a green manure, recognized as a viable alternative in the search for sustainability of agricultural soils. In this context, an experiment was implemented at the experimental farm of UFERSA, in order to evaluate the performance of green manuring legumes seeded in different rates, for improving soil quality and corn yield. The experiment was constituted of two stages: first, the cultivation of legume species and, second, commercial cultivation of corn. Experimental design was randomized blocks in a factorial scheme 4x4, with 16 treatments and four replications, totaling 64 plots, each of 1 m2. Factors studied were legume species (pigeon pea, jack bean, lab-lab, dwarf velvet bean) and seeding rates (10, 20, 30 and 40 plants m-2). Soil samples for analysis were taken before legume seeding and 30 days after its incorporation into the soil. At full flowering, legumes were cut, weighed for biomass determination, sampled for leaf analysis, incorporated into the soil and left fallow for 30 days. After this period corn crop was grown for determination of its nutritional status, plant height, dry mass of hundred grains and total mass of grains. Data were submitted to variance and regression analysis means were compared through Tukey test at a 5% probability level. Lab-lab and pigeon pea showed higher results of biomass accumulation and nutrient content, what provided improvement in soil chemical characteristics and¸ as a consequence, increased grains yield and plant height
Seeding densities of legumes in improving soil quality and yield of corn
Keywords: Zea mays L.; Green manure; Biomass; Zea mays L.; Adubação verde; Biomassa; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO